ANALISIS KESALAHAN SINTAKSIS PADA TEKS PERSUASI KARYA SISWA KELAS VIII SMP NEGERI 40 BANDUNG - M. Syamsul Ma'arif S. -; Dheni Harmaen; Meity Suratiningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The research aims to describe the causes of sentence writing errors in the persuasive text of class VIII SMP Negeri 40 Bandung, examine various forms of sentence writing errors, and attempt to make solutions to reduce sentence writing errors in persuasive texts by class VIII students of SMP Negeri 40 Bandung. The research data analysis technique uses the theory of Miles and Huberman in Sugiyono. The research method uses a qualitative approach. Based on the results of the research, it was found 76 sentence writing errors which included 2 unsubjected sentence errors, 5 unsubjected sentence errors, 16 unsubjected and unpredicated sentence errors, 12 subject doubling errors, 1 error between the predicate and the inserted object, 11 sentence errors that illogical, 9 errors in ambiguous sentences, 1 error in omission of conjunctions, 12 errors in the use of excessive conjunctions, 4 errors in the use of foreign terms, 3 errors in the use of unnecessary question words. Based on the results of interviewing one of the Indonesian language teachers at SMP Negeri 40 Bandung, it was concluded that the cause of errors in writing sentences in the persuasive text of class VIII students at SMP Negeri 40 Bandung, namely students did not understand the material and did not carry out an assessment or examination of the writing of sentences in student work. The solution to reduce sentence writing errors in persuasive texts by class VIII students of SMP Negeri 40 Bandung is to make interesting learning videos and carry out in depth assessments or examinations of sentence writing in students works.